2013
DOI: 10.1111/febs.12188
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of cell cycle progression distinguishes members of the myogenic regulatory factor family of transcription factors

Abstract: The muscle‐specific basic helix–loop–helix proteins MyoD, Myf5, myogenin (Myog) and MRF4 constitute the myogenic regulatory factor (MRF) family of transcription factors that drive muscle gene expression during myogenesis. Having evolved from a single ancestral gene, the spatial and temporal specificity of expression for each family member has been used to define a hierarchical relationship between the four MRFs. Molecular characterization of two of the MRFs (MyoD and Myog) suggests an important distinction bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
123
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 99 publications
(162 reference statements)
7
123
0
Order By: Relevance
“…2C-E). Thus, KAP1 is required for the expression of key MyoD and Mef2 target genes such as Myog, a factor that mediates the cell cycle exit and terminal differentiation of myoblasts (Liu et al 2012;Singh and Dilworth 2013).…”
Section: Kap1 Is Necessary For Myoblast Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…2C-E). Thus, KAP1 is required for the expression of key MyoD and Mef2 target genes such as Myog, a factor that mediates the cell cycle exit and terminal differentiation of myoblasts (Liu et al 2012;Singh and Dilworth 2013).…”
Section: Kap1 Is Necessary For Myoblast Differentiationmentioning
confidence: 99%
“…Interestingly, this subset of MyoD-recruiting genes is also enriched in Mef2 (myocyte enhancer factor 2) (Cao et al 2010), and, more generally, MyoD-and Mef2-binding elements are overrepresented in cis-regulatory modules (CRMs) active during muscle differentiation (Kwon et al 2011). MyoD and Mef2 also cooperate during muscle regeneration, where MyoD levels first increase in satellite cells, contributing to the expansion of these progenitors (Zhang et al 2010;Singh and Dilworth 2013) before initiating with Mef2 the myogenic gene expression program that leads to cell cycle exit and formation of functional multinucleated myotubes (Penn et al 2004;Liu et al 2012;Singh and Dilworth 2013). This is consistent with the recruitment by the two factors of a combination of coregulatory molecules necessary for activating the muscle gene expression pro- gram (Molkentin et al 1995;Rampalli et al 2007).…”
mentioning
confidence: 99%
“…Myogenin is an early marker for the entry of myoblasts into the differentiation pathway and possesses an antiproliferative activity. 46 Therefore, we have analyzed the myogenin expression as an early marker of differentiation and showed that NP treatment did not modify the level of myogenin expression, indicating that the effect of NPs is not directly related to the myogenin expression. Likewise, Hochreiter-Hufford et al 25 who reported on the promoting role of apoptosis on myoblast fusion, did not observe a modification of myogenin expression, suggesting that apoptosis is required either downstream or parallel to myogenin.…”
mentioning
confidence: 96%
“…These findings parallel those seen in myogenesis: the molecular characterization of MyoD and myogenin suggests that both factors play distinct roles in cell cycle modulation but act synergistically to drive muscle differentiation. For example, MyoD directly activates genes involved in cell cycle progression during myoblast proliferation, whereas myogenin induces anti-proliferative genes leading to cell cycle exit and myoblast differentiation (Singh and Dilworth, 2013). Intriguingly, unlike SPCH or FAMA overexpression, which only produces more ACDs and single GCs, respectively, MUTE overexpression directs differentiation to intact mature stoma, including in the flower petal epidermis, which does not normally produce stomata .…”
Section: Transcription Factors Regulating Stomatal Lineage Specificationmentioning
confidence: 99%